Study on electric energy consumed in intermittent series–parallel elastic actuators (iSPEA). (6th April 2017) - Mathijssen, Glenn; Furnémont, Raphaël; Verstraten, Tom; Espinoza, Cyprian; Beckers, Simon; Lefeber, Dirk; Vanderborght, Bram
Abstract: On compliant actuators, intermittent series–parallel elastic actuators (iSPEA) can reduce motor load by variable load cancellation through recruitment of parallel springs by a single motor. However, the potential to reduce electric energy consumed, compared to a traditional stiff driven joint has not yet been evaluated thoroughly both in simulations and experiments. We have developed a 1DOF MACCEPA-based iSPEA test bench with a self-closing intermittent mechanism. An iSPEA driven warehouse robot is used as a case study in simulation. A method to compare iSPEA and traditional actuators is proposed. This paper shows a match between our simulations and experimental results regarding electric energy consumed. Although the chosen gear ratio shows to be detrimental for both the stiff actuator and the iSPEA, the electric energy consumed by the iSPEA is about 25% to 67% of the stiff actuator, for a warehouse robot placing 3 objects on a shelf.